Different effects of abnormal mechanical stress on temporomandibular joint cartilage, subchondral bone, and discs - Xiao, Miao; Ni, Shilei (Frontiers in Physiology, 2025)
BackgroundTemporomandibular joint disorder (TMJD) is a group of diseases occurring in the temporomandibular joint (TMJ) with clinical manifestations of pain in the joint area, mastication disorders, and restriction of mouth opening, which is one of the most common diseases of the oral and maxillofacial region, and its specific etiology has not yet been fully elucidated. As a biomechanical orchestrator, the TMJ mediates dynamic transduction of masticatory forces during the functional loading cycle. Notably, as a secondary cartilage type, the condylar cartilage exhibits postnatal remodeling that is critically dependent on functional mechanical stimulation. Abnormal mechanical stimulation can result in structural dysfunction of the TMJ.ObjectiveThe purpose of this review was to outline the remodeling responses of TMJ cartilage, subchondral bone, and disc to abnormal mechanical stimulation of different types and intensities, especially the subchondral bone and articular disc.ConclusionAbnormal mechanical stress induces degeneration of the condylar cartilage, characterized by dysregulated chondrocyte proliferation and differentiation, elevated cell apoptosis, and ECM injury. The ability of TMJ condylar cartilage to adapt to changes in the mechanical load environment for remodeling is influenced by age, as well as the type, intensity, and duration of the applied mechanical load. Bone loss is often the first response of subchondral bone to abnormal mechanical forces. Abnormal mechanical stimuli affect nutrient supply and matrix metabolism of TMJ discs.